2017
DOI: 10.1212/wnl.0000000000003629
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of epilepsy/seizures as a comorbidity of neurologic disorders in nursing homes

Abstract: Objective: To determine the prevalence of epilepsy/seizure (epi/sz) comorbid with other neurologic disorders in elderly nursing home residents and to examine demographic and regional variability and associations with clinical characteristics.Methods: We studied 5 cross-sectional cohorts of all residents in any Medicare/Medicaid-certified nursing home in the United States on July 15 of each year from 2003 to 2007. Epi/sz was identified by ICD-9 codes (345.xx or 780.39) or check box (Minimum Data Set). Epi/sz pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…The number of elderly patients in the United States is rapidly increasing and is projected to be 71 million by 2030 [2]. The prevalence of epilepsy is higher in elderly nursing home residents than in any other cohort, with the point prevalence of an ICD-9 epilepsy/seizure code present in 7.8% of all elderly home nursing residents in the USA during 2007 [3]. Information regarding the patterns of antiseizure drug (ASD) use in this population is limited, and most of the available data is from studies reported more than a decade ago.…”
Section: 0 Introductionmentioning
confidence: 99%
“…The number of elderly patients in the United States is rapidly increasing and is projected to be 71 million by 2030 [2]. The prevalence of epilepsy is higher in elderly nursing home residents than in any other cohort, with the point prevalence of an ICD-9 epilepsy/seizure code present in 7.8% of all elderly home nursing residents in the USA during 2007 [3]. Information regarding the patterns of antiseizure drug (ASD) use in this population is limited, and most of the available data is from studies reported more than a decade ago.…”
Section: 0 Introductionmentioning
confidence: 99%
“…Interestingly, the participants from studies in this review were not gathered from nursing homes. However, the prevalence of epilepsy in older adults living in nursing homes is higher compared to communitydwelling older adults [46]. Birmbaun found that nursing home residents with epilepsy had poorer scores for activities of daily living, cognition and comorbidity burden.…”
mentioning
confidence: 99%
“…Patients were included in the analysis if they met the following criteria: (1) age C 4 years at index date; (2) C 1 prescription of ESL in the LTC pharmacy data at any time between 1 April 2014 and 31 December 2018 (i.e., the selection window); (3) deterministic linking of LTC pharmacy, prescription claims, and professional fee claims data from IQVIA's New Data Warehouse during the study period; (4) diagnosis of FS in professional fee claims or CDM (International Classification of Diseases, 9th Revision, Clinical Modification [ICD-9-CM] codes: 345.4X, 345.5X; ICD-10-CM codes: G40.0x, G40.1x, G40.2x) [24] during the 12 months prior to the index date (pre-index/baseline period), and including the index date; (5) activity in the 12-month pre-and post-index periods, defined as C 1 professional fee claim and C 1 prescription (LTC pharmacy database or prescription claims) as a proxy for continuous enrollment; (6) pharmacy stability in the LTC pharmacy database or prescription claims in the 12-month pre-and post-index periods, defined as consistent reporting of data from the pharmacy most frequently visited by the patient and C 80% coverage rate for each month in the 12-month pre-and post-index periods.…”
Section: Patient Populationmentioning
confidence: 99%